2024
DOI: 10.1038/s41467-024-45503-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional nanoporous graphene superlattice

Hualiang Lv,
Yuxing Yao,
Mingyue Yuan
et al.

Abstract: Two-dimensional (2D) superlattices, formed by stacking sublattices of 2D materials, have emerged as a powerful platform for tailoring and enhancing material properties beyond their intrinsic characteristics. However, conventional synthesis methods are limited to pristine 2D material sublattices, posing a significant practical challenge when it comes to stacking chemically modified sublattices. Here we report a chemical synthesis method that overcomes this challenge by creating a unique 2D graphene superlattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…To reveal the EM wave-absorption behavior and mechanism of the composite aerogel, the relevant electromagnetic parameters for FMGM-X and GM were further analyzed. Generally, the real and imaginary parts of complex permittivity ( ε′ and ε″ ) correspond to the energy storage and dissipation capacities in electric fields, respectively. Figure a shows the ε′ curves for samples across the frequency from 2 to 18 GHz. It can be found that an increase in Fe 3 O 4 /MoS 2 concentration significantly reduces the ε′ values of the aerogel, which can be ascribed to the decreased proportion of carbon materials.…”
Section: Resultsmentioning
confidence: 99%
“…To reveal the EM wave-absorption behavior and mechanism of the composite aerogel, the relevant electromagnetic parameters for FMGM-X and GM were further analyzed. Generally, the real and imaginary parts of complex permittivity ( ε′ and ε″ ) correspond to the energy storage and dissipation capacities in electric fields, respectively. Figure a shows the ε′ curves for samples across the frequency from 2 to 18 GHz. It can be found that an increase in Fe 3 O 4 /MoS 2 concentration significantly reduces the ε′ values of the aerogel, which can be ascribed to the decreased proportion of carbon materials.…”
Section: Resultsmentioning
confidence: 99%